Human intestinal epithelial cells secrete interleukin-1 receptor antagonist and interleukin-8 but not interleukin-1 or interleukin-6. Issue 3 (1st March 2000) - Daig, R; Rogler, G; Aschenbrenner, E; Vogl, D; Falk, W; Gross, V; Schölmerich, J; Andus, T
Abstract : BACKGROUND: There is growing evidence that intestinal epithelial cells (IECs) are involved in the mucosal immune system. AIM: To assess the pattern of cytokines secreted by IECs and lamina propria mononuclear cells (LPMNCs). To achieve this, the expression and secretion of interleukin (IL)-1, IL-1 receptor antagonist (IL-1ra), IL-6, and IL-8 in human primary colonic and ileal IECs and LPMNCs from the same patient were studied. METHODS: IECs and LPMNCs were isolated from surgical specimens or endoscopic biopsy samples. mRNA expression was investigated by northern blot analysis. Secretion of IL-1β, IL-6, IL-8, and IL-1ra was measured by enzyme linked immunosorbent assay. RESULTS: IL-1ra mRNA levels were higher in IECs than in LPMNCs in all probands. IL-8 mRNA was only present in low amounts in the IECs from two controls. In none of the specimens were IL-1β and IL-6 mRNA present in IECs. Transcripts encoding IL-1β, IL-1ra, IL-6, and IL-8 were identified in LPMNC preparations of all specimens. IECs from normal mucosa produced no detectable amounts of IL-1β or IL-6, whereas LPMNCs did. IECs secreted some IL-8 (65 (9) pg/10 5 cells) but significantly more was generated by LPMNCs (408 (43) pg/10 5 cells, p<0.0001). However, IECs secreted more IL-1ra than did LPMNCs (120 (12) v 94 (11) pg/10 5 cells). In acute inflammation, IEC IL-1ra secretion was significantly increased. A correlation between secreted IL-1ra and the macroscopical degree of inflammation was found in Crohn's disease ( r = 0.64, p<0.0001, n = 36) and ulcerative colitis ( r = 0.76, p<0.0001, n = 24). CONCLUSIONS: IECs from normal mucosa express and secrete IL-1ra and low amounts of IL-8, but no IL-1 or IL-6. In inflamed mucosa the secretion of IL-1ra by IECs is slightly increased but may be not sufficient to antagonise the greatly increased production of proinflammatory cytokines by LPMNCs and the IECs themselves.